Polymorphism and exercise performance - Wolfarth, B. (European Journal of Sport Science, 2001)
The fields of molecular genetics and molecular biology are of increasing interest in medicine and science. The aim of this article is to describe the current status of genetics in sports, with a special focus on genetic polymorphisms and endurance performance. Results from twin studies suggested a high percentage of heritability for endurance performance and maximal oxygen uptake (VO2max). Data from large sample sizes of monozygotic and dizygotic twins showed heritability values up to 40% for adjusted VO2max values. Today we are able to use molecular markers to look for specific genes and their implications for phenotypes of interest. The first results for endurance-related phenotypes are available now. Till now we have evidence for association between different types of endurance measures and polymorphisms in the genes encoding the Angiotensin-Converting-Enzyme (ACE), the muscle type Creatine-Kinase (CKMM), and the alpha-2a-adrenoceptor (ADRA2A) gene. The scientific focus in the next years will mainly involve case-control studies and genome analysis with informative markers in known and unknown genes (regions) of interest.